Tìm x, biết: x3-x2=4x2-8x+4
Tìm x, biết: x 3 – x 2 = 4 x 2 – 8 x + 4
Ta có: x3 – x2= x2(x -1); 4x2 – 8x + 4 = 4(x2 – 2x + 1) = 4(x – 1)2
Vậy x2 (x -1) = 4(x – 1)2 ⇒ x2(x -1) - 4(x – 1)2 = 0
⇒ (x – 1)(x2 – 4x + 4) = 0 ⇒ (x – 1)(x – 2)2 = 0
⇒ x – 1 = 0 hoặc x – 2 = 0 ⇒ x = 1 hoặc x = 2.
Bài 5. Tìm x, biết:
a) x (2x - 7) + 4x -14 = 0
b) x3 - 9x = 0
c) 4x2 -1 - 2(2x -1)2 = 0
d) (x3 - x2 ) - 4x2 + 8x - 4 = 0
\(a,\Leftrightarrow x\left(2x-7\right)+2\left(2x-7\right)=0\\ \Leftrightarrow\left(x+2\right)\left(2x-7\right)=0\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=\dfrac{7}{2}\end{matrix}\right.\\ b,\Leftrightarrow x\left(x^2-9\right)=0\\ \Leftrightarrow x\left(x-3\right)\left(x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=3\\x=-3\end{matrix}\right.\\ c,\Leftrightarrow\left(2x-1\right)\left(2x+1\right)-2\left(2x-1\right)^2=0\\ \Leftrightarrow\left(2x-1\right)\left(2x+1-4x+2\right)=0\\ \Leftrightarrow\left(2x-1\right)\left(-2x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=\dfrac{3}{2}\end{matrix}\right.\\ d,\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\\ \Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\\ \Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
tìm x
x6 +2x3+1=0
x(x-5)=4x-20
x4-2x2=8-4x2
(x3-x2)-4x2+8x-4=0
\(x^6+2x^3+1=0\)
\(\Leftrightarrow\left(x^3\right)^2+2x^3+1=0\)
\(\Leftrightarrow\left(x^3+1\right)^2=0\)
\(\Leftrightarrow x^3=\left(-1\right)^3\)
\(\Leftrightarrow x=-1\)
___________
\(x\left(x-5\right)=4x-20\)
\(\Leftrightarrow x\left(x-5\right)-4\left(x-5\right)=0\)
\(\Leftrightarrow\left(x-5\right)\left(x-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=4\\x=5\end{matrix}\right.\)
_____________
\(x^4-2x^2=8-4x^2\)
\(\Leftrightarrow x^2\left(x^2-2\right)+\left(4x^2-8\right)=0\)
\(\Leftrightarrow x^2\left(x^2-2\right)+4\left(x^2-2\right)=0\)
\(\Leftrightarrow\left(x^2-2\right)\left(x^2+4\right)=0\)
\(\Leftrightarrow x^2=2\)
\(\Leftrightarrow x=\pm\sqrt{2}\)
_______________
\(\left(x^3-x^2\right)-4x^2+8x-4\)
\(\Leftrightarrow x^2\left(x-1\right)-4\left(x^2-2x+1\right)=0\)
\(\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
Tìm x:
a)x.(2x-7)+14=4x
b)25x3=2x
c)(x-5)3=x3-125
d)(x3-x2)-4x2+8x-4=0
Tìm x:
a)x.(2x-7)+14=4x
b)25x3=2x
c)(x-5)3=x3-125
d)(x3-x2)-4x2+8x-4=0
Tìm x:
a) 36x3-4x=0
b) 3x(x-2)-2+x=0
c) (x3-x2)-4x2+8x-4=0
d) x2-6x-16=0
e) x4-6x2-7=0
Tìm x:
a) 36x3-4x=0
b) 3x(x-2)-2+x=0
c) (x3-x2)-4x2+8x-4=0
d) x2-6x-16=0
e) x4-6x2-7=0
(Mình cần gấp ạ)
a) Ta có: \(36x^3-4x=0\)
\(\Leftrightarrow4x\left(9x^2-1\right)=0\)
\(\Leftrightarrow x\left(3x-1\right)\left(3x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{1}{3}\\x=\dfrac{-1}{3}\end{matrix}\right.\)
b) Ta có: \(3x\left(x-2\right)+x-2=0\)
\(\Leftrightarrow\left(x-2\right)\left(3x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{-1}{3}\end{matrix}\right.\)
d) Ta có: \(x^2-6x-16=0\)
\(\Leftrightarrow\left(x-8\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=8\\x=-2\end{matrix}\right.\)
e) Ta có: \(x^4-6x^2-7=0\)
\(\Leftrightarrow\left(x^2-7\right)\left(x^2+1\right)=0\)
\(\Leftrightarrow x\in\left\{\sqrt{7};-\sqrt{7}\right\}\)
Bài 1: Tìm nghiệm của các đa thức sau:
a) x + 7; b) x – 4; c) –8x + 20; d) x2 – 100;
e) 4x2 – 81; f) x2 – 7; g) x2 – 9x; h) x3 + 3x.
.Tìm x biết:
a) 3x(x – 2) – x + 2 = 0
b) x3 – 6x2 + 12x – 8 = 0
c) 16x2 – 9(x + 1)2
d) x2 (x – 1) – 4x2 + 8x – 4 = 0
\(a,\Leftrightarrow\left(x-2\right)\left(3x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\\ b,\Leftrightarrow\left(x-2\right)^3=0\Leftrightarrow x-2=0\Leftrightarrow x=2\\ c,\Leftrightarrow\left(4x-3x-3\right)\left(4x+3x+3\right)=0\\ \Leftrightarrow\left(x-3\right)\left(7x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{3}{7}\end{matrix}\right.\\ d,\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\\ \Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\\ \Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
3. Tìm nghiệm của các đa thức sau:
a) x + 7; b) \(\dfrac{1}{2}\)x - 4; c) - 8x + 20; d) x2 -100;
e) 4x2 -81; f) x2 - 7; g) x2 - 9x; h) x3 + 3x.
b: 1/2x-4=0
=>1/2x=4
hay x=8
a: x+7=0
=>x=-7
e: 4x2-81=0
=>(2x-9)(2x+9)=0
=>x=9/2 hoặc x=-9/2
g: x2-9x=0
=>x(x-9)=0
=>x=0 hoặc x=9
a)\(x+7=0=>x=-7\)
b)\(\dfrac{1}{2}x-4=0=>\dfrac{1}{2}x=4=>x=8\)
c)\(-8x+20=0=>-8x=-20=>x=\dfrac{5}{2}\)
d)\(x^2-100=0=>x^2=100=>\left[{}\begin{matrix}x=10\\x=-10\end{matrix}\right.\)
e)\(4x^2-81=0=>4x^2=81=>x^2=\dfrac{81}{4}=>\left[{}\begin{matrix}x=\dfrac{9}{2}\\x=-\dfrac{9}{2}\end{matrix}\right.\)
f)\(x^2-7=0=>x^2=7=>x=\sqrt{7}\)
g)\(x^2-9x=0=>x\left(x-9\right)=0=>\left[{}\begin{matrix}x=0\\x=9\end{matrix}\right.\)